ANALYSIS OF SECURITY CHALLENGES IN REST API IN EDGE COMPUTING-BASED IOT ECOSYSTEM: A REVIEW - Rudolf Sinaga; Samsinar Samsinar; Soomal Fatima; Frangky Frangky (JIKO (Jurnal Informatika dan Komputer), 2025)
REST APIs are the backbone of data communication in the Internet of Things (IoT)-based edge computing ecosystem because they are lightweight and flexible. However, the REST architecture's openness and the edge devices' limited resources give rise to security challenges such as MITM, spoofing, and replay attacks. This study aims to identify the key challenges of REST API security in IoT edge environments, evaluate the limitations of conventional solutions such as TLS and RSA/ECDSA algorithms, and explore the potential of Post-Quantum Signature-based digital authentication approaches (PQS). Through a comprehensive narrative literature review of 43 peer-reviewed publications (2020-2025), this research reveals two key findings: the results show that TLS generates significant overhead in memory and energy, while classical algorithms do not resist quantum threats. PQS schemes such as Falcon and Dilithium have proven more efficient and secure in limited devices. The study concludes that PQS-based lightweight authentication approaches have strong prospects for implementation in future REST API gateway architectures, particularly in supporting electronic-based governance systems (SPBEs).